2006
DOI: 10.1002/masy.200650604
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of PEG in the Warship Vasa

Abstract: The distribution and ageing of polyethylene glycol (PEG) in the Vasa warship has been examined and compared with other archaeological shipwrecks which have also been impregnated with PEG. The distribution of the PEG has been characterised using a variety of mass spectrometric and FT‐IR techniques. Our results show that the PEG after 30 years is still in a reasonably good condition, with a molecular weight distribution that resembles fresh PEG. Only minor levels of degradation products were found. It seems that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 9 publications
1
30
0
1
Order By: Relevance
“…Researchers at the Danish Technical University have studied methods to analyse the long-term behaviour of PEG by applying an accelerated ageing procedure. This method allows the estimation of the long-term stability of the consolidant material (Glastrup et al, 2006a(Glastrup et al, , 2006bMortensen, 2009).…”
Section: Accelerated Ageing Of the Potential Consolidant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers at the Danish Technical University have studied methods to analyse the long-term behaviour of PEG by applying an accelerated ageing procedure. This method allows the estimation of the long-term stability of the consolidant material (Glastrup et al, 2006a(Glastrup et al, , 2006bMortensen, 2009).…”
Section: Accelerated Ageing Of the Potential Consolidant Materialsmentioning
confidence: 99%
“…In particular, these reports focus on the degradation of PEG to acidic by-products over time, its utility as a solid-state ion transporter (Glastrup et al, 2006a(Glastrup et al, , 2006bMortensen et al, 2007;Mortensen, 2009), and the plasticising effect it can have on already fragile archaeological wood (Bardet et al, 2007). Recent work suggests that polysaccharides and oligoamides are the most suitable alternatives to synthetic treatments such as PEG (Cipriani et al, 2010(Cipriani et al, , 2013Christensen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…6 However, within its moist oak wood signs of degradation of PEG and hemicellulose, catalyzed by iron(II) ions, have been reported. 7,8 Modern analytical techniques are valuable for investigating the chemical state and monitoring the mechanical stability of marine archaeological wood in major conserved artifacts, and in particular the development of synchrotron-based X-ray absorption spectroscopic techniques has contributed with new insights. However, such analyses are also important before or at the time when the artifact is removed from an oxygen-depleted seabed environment in order to adapt the conservation treatment to the unique state of each object.…”
Section: Waterlogged Wood In Historical Shipwrecksmentioning
confidence: 99%
“…Many reports describe qualitative changes in FT-IR spectra related to decay of wood over long periods of exposure. 33 The PEG content in samples of marine-archaeological wood has also been analyzed with FT-IR, 8 in combination with Raman spectroscopy.…”
Section: ·2 Fourier-transform Infrared (Ft-ir) Spectroscopymentioning
confidence: 99%
“…This procedure aimed at replacing the water in the wood cell walls by PEG and thus preventing shrinkage and formation of cracks during drying (Håfors 2001). Since salt precipitation on numerous surfaces on the ship had been reported (Sandström et al 2002), a series of investigations of the chemistry (Glastrup et al 2006;Almkvist and Persson 2008a, b;Lindfors et al 2008;Almkvist et al 2016) and also of the mechanical properties of Vasa oak wood (Ljungdahl 2006;Bjurhager et al 2012;Vorobyev et al 2016) have been performed over the last years. These research activities showed that the oak wood is affected by degradation, i.e., by depolymerization of polysaccharides.…”
Section: Introductionmentioning
confidence: 99%